The Effect of Timing of Concurrent Chemoradiation in Patients With Newly Diagnosed Glioblastoma. Issue 2 (7th April 2015) - Han, Seunggu J.; Rutledge, W. Caleb; Molinaro, Annette M.; Chang, Susan M.; Clarke, Jennifer L.; Prados, Michael D.; Taylor, Jennie W.; Berger, Mitchel S.; Butowski, Nicholas A.
Abstract: BACKGROUND: The effect of timing of initiation of concurrent radiation and chemotherapy after surgery on outcome of patients with glioblastoma (GBM) remains unclear. OBJECTIVE: To further explore this issue, we analyzed 4 clinical trials for patients newly diagnosed with GBM receiving concurrent and adjuvant temozolomide. METHODS: The cohort study included 198 adult patients with newly diagnosed supratentorial GBM who were enrolled from 2004 to 2010 in 4 clinical trials consisting of radiation plus temozolomide and an experimental agent. The interval to initiation of therapy was determined from the time of surgical resection. The partitioning deletion/substitution/addition algorithm was used to determine the cutoff points for timing of chemoradiation at which there was a significant difference in overall survival (OS) and progression-free survival (PFS). RESULTS: The median wait time between surgery and initiation of concurrent chemoradiation was 29.5 days (range, 7-56 days). A short delay in chemoradiation administration (at 30-34 days) was predictive of prolonged OS (hazard ratio [HR]: 0.63, P = .03) and prolonged PFS (HR: 0.68, P = .06) compared with early initiation of concurrent chemoradiation (<30 days), after adjusting for protocol and baseline prognostic variables including extent of resection by multivariate analysis. A longer delay to chemoradiation beyond 34 days was not associated with improved OS or PFS compared with early initiation (HR: 0.94, P = .77 and HR: 0.91, P = .63, respectively). CONCLUSION: A short delay in the start of concurrent chemoradiation is beyond the classic paradigm of 4 weeks post-resection and may be associated with prolonged OS and PFS.